Risk factors for recurrence of suicide attempt - Silva, Daniel Augusto da (2022)
Objective: to analyze risk factors for recurrence of suicide attempt in people treated at the Emergency Care Unit in Assis, SP, Brazil. Method: quantitative study, participants who attempted suicide and attended at the reference unit. Individual interviews took place between December 2017 and November 2019. Divided into first-time suicide attempters and repeat offenders. Fisher's exact test, t-Student test for two samples and Multiple Logistic Regression Analysis were used. Results: 113 participants, being 80 (70.8%) repeat offenders, as they stated a previous history of suicide attempt and 33 (20.2%) being the first time. Conclusion: The age group from 20 to 47 years old, the self-perception of experiencing negative family relationships, the existence of mental disorder, the existence of chronic non-communicable diseases and people without a history of suicide attempt in the family were the risk factors associated with statistics for the occurrence of recidivism in suicide attempts.